The Implementation of Regional Policies Related to Sharia Financial Institutions in Lhokseumawe - Nurul Kamaly; Nazaruddin Nazaruddin; Nurul Fajri (Journal of Governance and Social Policy, 2022)
One of the advantages of the Province of Nanggroe Aceh Darussalam is the Shari'a legal framework included in Law No. 11 of 2006 governing Aceh's administration. This study examines the role of the Indonesian Islamic Bank Lhokseumawe Area in the implementation of Qanun Number 11 of 2018 concerning Islamic Financial Institutions. Bank Syariah Indonesia (BSI) Lhokseumawe Area contributed to applying the Qanun for Islamic Financial Institutions starting from account migration, socialization of sharia products, sharia services and also signing of cooperation agreements with partners to use products from sharia banking. One of the focuses of BSI Lhokseumawe Area in the process of integrating service operational systems in the Aceh region is the customer migration process from the original bank to Bank Syariah Indonesia. This migration process can be done online through BSI Mobile or face-to-face. ATM cards, mobile and internet banking. In this process, the convenience and security of customer data are prioritized. The implementation of the qanun does not necessarily go well, there are obstacles faced in the process of implementing the qanun. Implementing Islamic financial services requires the attention and hard work of all parties and not only the bank. Stakeholders and citizens can continue to be patient and continue to encourage, and provide support to these financial institutions in correcting the weaknesses that occur so that with the presence of the Indonesian Sharia Bank, they can improve sharia economic growth and also for the benefit of the people.